IBU DAN ANAK DALAM KARYA LUKIS IMPRESIONISME - SRI WAHYUNI, Drs. Erfahmi,M.Sn, Dr. Ramalais Hakim, M.Pd (Universitas Negeri Padang, 2014)
The purpose ofthis workis(1) describe thenatureofa mother, (2) how to educate childrenin accordancewith theIslamicShariah. Discussion ofthis thesisisaboutthe love thata mothershouldbe given(core) tohis son. Sourcesofthis thesisisfromthe surrounding environmentandthe phenomenonofdeviantbehaviororactsof violencefroma mothertoher child. Datacollectedwith theexperience gainedfrom thesurroundingenvironment anddiluarenvironment. By usinginformationfromphenomenathat existbothwithin theownand outsideenvironment. The findings ofthis workof tenworks, toexplainabout the beauty ofa mother's loveifsemuahnyagivenwithfull assuranceof hopefroma child.Kata kunci: Mother. And. child. In.This. Of. Impresionisme